Geomorphology of the Arrábida Chain (Portugal) - Fonseca, A.F. (2017)
Geomorphological maps are crucially important in geomorphology studies, allowing the representation of topographic and geological data in an interpretative, dynamic and appealing way. In this paper, a medium-scale (1:70,000) geomorphological map is presented with the objective of facilitating the analysis and interpretation of the Plio-Quaternary landscapes of the Arra´bida Chain, central-west Portugal. The map results from the combination of field and laboratory techniques, including aerial-photo interpretation, digital terrain data analysis and the morphometric study of landforms.